Ubogacający wymiar wiary w świetle encykliki Lumen fidei - Henryk Wejman (Colloquia Theologica Ottoniana, 2014)
The content of the article focuses on presenting the role and value of faith in the life and action of man in the light of the Encyclical of Pope Francis Lumen fidei. For this specific purpose has been achieved, first defined the concept of faith. Pope Francis defines faith as a response to the Word of God addressed to man (cf. LF 8). The response from the man is a consequence to the prior granting of God through Christ in the Holy Spirit (cf. LF 4). Therefore, faith is first – says the Pope – a gift from God , and then an act of intellectual and volitional human. It is born from the encounter with Him (cf. LF 4). Determination of the essence of faith enabled the next step in the reflection. It was the unveiling of the dynamic posture of faith man. The first factor is the acceptance of this dynamism on the part of a man’s own limitations and humble acceptance of God’s giving of. Another factor that accelerates the attitude of a man of faith is prayer. The harder man prays, the deeper becomes his faith. Shaped in such a way that the attitude of a man of faith has an impact on its performance. This effect manifests itself in a sturdy carrying out daily tasks, creating a brotherhood between people, building community spirit of love in the family and in the upbringing of children, zeal and respect for the environment.